2014
DOI: 10.1089/ten.tea.2013.0268
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Vascular Smooth Muscle Cell Phenotype in Three-Dimensional Coculture System by Jagged1-Selective Notch3 Signaling

Abstract: The modulation of vascular smooth muscle cell (VSMC) phenotype is an essential element to fabricate engineered conduits of clinical relevance. In vivo, owing to their close proximity, endothelial cells (ECs) play a role in VSMC phenotype switching. Although considerable progress has been made in vascular tissue engineering, significant knowledge gaps exist on how the contractile VSMC phenotype is induced at the conclusion of the tissue fabrication process. The objectives of this study were as follows: (1) to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 66 publications
2
28
0
Order By: Relevance
“…Our observations are in agreement with previous findings that in co-culture, ECs inhibited SMC proliferation, migration, and collagen synthesis, and supported SMC contractile phenotype [28][29][30]. Furthermore, it has been shown that in co-culture, HCAECs could increase the expression of SM-22α and calponin in HCASMCs [12], suggesting a regulatory role of intercellular contacts with HCAECs in HCASMC differentiation. Moreover, when cocultured on the opposite sides of Transwell membranes, ECs and SMCs were shown to form myoendothelial gap junctions [9,28], through which ECs could directly communicate with SMCs and regulate their functional activity [31].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our observations are in agreement with previous findings that in co-culture, ECs inhibited SMC proliferation, migration, and collagen synthesis, and supported SMC contractile phenotype [28][29][30]. Furthermore, it has been shown that in co-culture, HCAECs could increase the expression of SM-22α and calponin in HCASMCs [12], suggesting a regulatory role of intercellular contacts with HCAECs in HCASMC differentiation. Moreover, when cocultured on the opposite sides of Transwell membranes, ECs and SMCs were shown to form myoendothelial gap junctions [9,28], through which ECs could directly communicate with SMCs and regulate their functional activity [31].…”
Section: Discussionsupporting
confidence: 93%
“…Myoendothelial gap junctions can be mimicked in vitro by co-culturing ECs and SMCs on the opposite sides of a porous membrane; this model have been widely used to study the mechanisms of cell-cell interaction in the vasculature. Thus, it has been reported that in human coronary artery SMCs (HCASMCs) co-cultured with human coronary ECs (HCAECs), differentiation markers were significantly induced, indicating a regulatory role of EC-SMC intercellular contacts in SMC phenotypic switching [12]. Furthermore, in a static ECs-SMCs co-culture model using Transwell inserts, myoendothelial gap junctions have been shown to modulate the differentiation of pulmonary arterial SMCs [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, studies investigating the function of Notch signaling in pericyte/vSMC have yielded conflicting results, describing both anti-proliferation and pro-proliferation functions as well as both anti-maturation and pro-maturation functions for Notch [26,27]. These discrepancies have been speculated to be a result of the highly context-dependent nature and tight spatio-temporal regulation of Notch pathway components during vascular development [9].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Bhattacharya et al developed a coculture of human coronary artery cells in 3D poly(carbonate urethane) scaffolds to investigate EC-mediated Notch signaling and induction of SMC contractile phenotype. 50 These studies led to a critical understanding of the benefits of cocultures, mechanical stimuli, and 3D scaffolds to mimic physiological conditions, and investigated biological mechanisms under more controlled environments. Our current experimental setup differs from these previous studies as follows: (1) collagen gels were used in this study compared with synthetic polymeric scaffolds tested in previous studies; (2) human aortic ECs were cultured within 3D scaffolds in our study instead of a confluent monolayer, to enable paracrine signaling between ECs and SMCs; and (3) the microfluidic setup developed here would allow diffusion of paracrine signals and exogenous molecules under controlled static or dynamic flow conditions, depending on the experimental need.…”
Section: Resultsmentioning
confidence: 99%